PELATIHAN MANAJEMEN KEUANGAN UNTUK MENINGKATKAN LITERASI KEUANGAN BAGI CALON GURU UNIVERSITAS ABDURACHMAN SALEH SITUBONDO - Lisana Oktavisanti; Dwi Herlindawati; Riza Afita Surya (Jubaedah : Jurnal Pengabdian dan Edukasi Sekolah (Indonesian Journal of Community Services and School Education), 2021)
This community service activity is carried out with the target students of the Abdurahman Saleh University Elementary School Teacher Education Study Program Situbondo. Partner problems that are a priority and need to be resolved through this PKM program are (1) the low level of financial literacy among students, (2) knowledge and understanding of the concept of assets and liabilities, (3) knowledge and understanding of the time value of money, and (4) knowledge and understanding of the concept of risk in finance. The solutions to be achieved include: (1) providing training on the concept of assets and liabilities, (2) providing training on the time value of money, (3) providing training on the concept of risk in finance. The expected outcomes of this PKM activity are (1) increased knowledge and understanding of the concept of assets and liabilities, (2) increased knowledge and understanding of the time value of money, (3) increased knowledge and understanding of the concept of risk in finance, (4) Able to make personal financial planning